1981
DOI: 10.1002/bjs.1800680103
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of ileorectal anastomosis in Crohn's disease

Abstract: A total of 105 patients have been treated with colectomy and ileorectal anastomosis from 1958 to 1978 in Birmingham, England (48) and in Leiden, Netherlands (57). At the end of 1978 the mean follow-up was 7.6 years (6 months-20 years). Mild or moderate degrees of proctitis were not considered as contraindications for ileorectal anastomosis. The presence or absence of ileal disease or perianal disease at the time of ileorectal anastomosis did not effect the long term prognosis but patients with sigmoidoscopic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 10 publications
1
18
0
1
Order By: Relevance
“…Many authors reported similar findings, with the rate of proctectomy after IRA ranging between 11 and 32% (table 3) [19,20,21,22,23,24,25]. …”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Many authors reported similar findings, with the rate of proctectomy after IRA ranging between 11 and 32% (table 3) [19,20,21,22,23,24,25]. …”
Section: Discussionmentioning
confidence: 58%
“…In a study with a mean follow-up of 7.5 years, Buchmann et al [19] showed that 20% of 105 patients with IRA underwent a total proctectomy. Many authors reported similar findings, with the rate of proctectomy after IRA ranging between 11 and 32% (table 3) [19,20,21,22,23,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some patients, the recurrence may be confined to the small bowel, so a further resection and anastomosis is possible. Thus, approximately 75% of patients may have a functioning IRA at 5 years and 50% at 10 years [25][26][27][28].…”
Section: Surgery For Large Bowel Diseasementioning
confidence: 99%